The use of Mother Tongue in the classroom of Spanish as a Foreign Language: a study in an 11th level class - Santos, Sara (2020)
This article focuses on the use of Mother Tongue (MT) in Foreign Language (FL) classroom and aims at understanding its educational potential through an analysis of the speech of 11th level students of Humanities at the class of Spanish Initiation in a school in the district of Aveiro. The aim of this study is to identify the processes of use of MT in students’ oral speech, being identified the following two: transference, which consists of using the MT to understand Foreign Language (FL); and interference, which implies a transportation of structures from the MT to the FL. After the consideration of the theories around the topic, we developed this case study by using observation grids and record and transcription of four Spanish lessons during the school year of 2018/2019 as forms of data collection. With the results, we concluded that the students seem to use MT for functional communication purposes to understand organizational aspects of the lesson and of its activities, as well as to express their opinions about the themes of the unit. There is also use of MT for transference, which occurs, mostly, in moments of translation, requests of translation and validation of what students think the words/expressions mean. Although it presents less interventions, we should also consider the use of MT as interference, mostly when students pronounce Spanish words in a Portuguese accent, as well as when it occurs the wrong construction of Spanish syntax.